Palladium-catalyzed C(sp3)–H nitrooxylation of masked alcohols. Issue 1 (30th November 2022) - Xue, Yuan; Zhou, Ruo-Bing; Luo, Jun; Hu, Bing-Cheng; Liu, Zhong-Quan; Jiang, Chao
Abstract : A palladium-catalyzed β-C(sp 3 )–H nitrooxylation of aliphatic alcohols with AgNO2 is reported. Various nitrooxylated alcohols could be obtained and converted into 1, 2-diol and 1, 2-amino alcohol. Abstract : A palladium-catalyzed β-C(sp 3 )–H nitrooxylation of aliphatic alcohols with AgNO2 is reported. An 8-formylquinoline-derived oxime is installed as an exo -type directing group for sp 3 C–H activation and selectfluor acts as the oxidant. The reaction tolerates a variety of functional groups and shows good selectivity for β-C–H nitrooxylation of alcohols.